The Influence of Ceo Reputation, Company Reputation And The Auditor's Reputation To Financial Distress - Rifdah Riyan Dara; Ahmad Saputra; Sovia Lolita Apriani Pardede (Jurnal Mantik, 2022)
This research aims to examine and analyze the effect of CEO reputation, company reputation and auditor reputation on financial difficulties. The dependent variable, namely financial difficulties, is measured using a dummy variable with a binomial measure, namely (1) if the company is experiencing financial difficulties and zero (0) if the company is not experiencing financial difficulties. If the condition of the company meets at least one of these requirements, it is given a value of 1 (experiencing financial difficulties) and if it does not meet at least one condition, it is considered not experiencing financial difficulties which is then given a value of 0. While the independent variable, namely the CEO's reputation is measured by data envelopment analysis (DEA), then the reputation of the company using the GRI guidelines, is given a value of 1 if there is a company reputation dimension and a value of 0 (zero) if there is none, then the scores are summed based on the dimensions of the company's reputation and auditor reputation using a dummy variable. If the company uses the services of a KAP that is affiliated with The Big Four Auditor KAP, it is given a code of 1. Meanwhile, if the company uses the services of a KAP that is not affiliated with the Big Four Auditor KAP, it is given a code of 0. The third stage was data analysis with logistic regression analysis.84 companies listed on the IDX were used as a sample and then logistically analyzed using the SPSS program since the variables used a dummy measure. The results of this research succeeded in proving that the reputation of the CEO and the reputation of the company had a negative effect on financial difficulties, thus the better the reputation of the CEO and the company, the lower the financial difficulties. However, the auditor's reputation has no effect on financial difficulties. The management will assume that regardless of the reputation of the auditors chosen by the company will still give the sinilar opinion regarding the company's financial condition.